PENGENTASAN BUTA HURUF AL-QUR’AN DI SMP MUHAMMADIYAH 1 SLEMAN - Muhammad Irfandi Rahman (PAI RAFAH, 2019)
Muhammadiyah is one of the socio-religious organizations whose activities are always based on the spirit of da’wah. The field of education as one of the fields cultivated by Muhammadiyah continues to experience development over time. This was marked by the increasing number of Muhammadiyah educational institutions. One of the Muhammadiyah educational institutions was SMP Muhammadiyah 1 Sleman. This school is a Muhammadiyah school that promotes religious coaching programs in order to achieve Graduates’ Competency Standars (SKL) determined by the Muhammadiyah Central and Secondary Education Board. One of the competencies of SMP/MTs Muhammadiyah/ graduates is being able to read the Quran well, interpret and memorize 1 (one) juz. Of course the achievement of SKL is not easy because SMP Muhammadiyah 1 Sleman faced the fact that most students input in the 2018/2019 Academic Year cannot yet read the Quran. This is certainly not a trivial problem. This problem received special attention from the school so that graduates could achieve SMP/MTs Muhammadiyah SKL, especially in terms of the ability to read the Quran. This paper attempts to explain the effort of SMP Muhammadiyah 1 Sleman in alleviating the Qur'an illiteracy of class VII students. The method used in this paper is observation, interview, and documentation. The results of this study are: (1) The school effort in alleviating the Qur'an's illiteracy is to hold religious coaching activities, namely: Reading-Write the Qur'an (BTAQ), Mabit, and morning tadarus; (2) The results of the implementation of these activities are an increase in the number of students who have been able to read the Qur'an, from the previous 23 (19.83%) to 49 (42.24%).